Internet Advertising: Technology, Ethics, and a Serious Difference of Opinion. - WICKER, STEPHEN B.; KARLSSON, KOLBEINN (Communications of the ACM, 2017)
The article discusses the functions and workings of Internet advertising networks Internet advertising blockers and examines various opinions on the morality and ethics of ad blocking, particularly a view of ad blocking as theft and a view of ad blocking as preventing excessive consumption. It discusses the use of HTML code, data management platforms (DMPs), and supply-side platforms (SSPs).